2010
DOI: 10.1074/jbc.m109.079830
|View full text |Cite
|
Sign up to set email alerts
|

Proteoliposomes Harboring Alkaline Phosphatase and Nucleotide Pyrophosphatase as Matrix Vesicle Biomimetics

Abstract: We have established a proteoliposome system as an osteoblast-derived matrix vesicle (MV) biomimetic to facilitate the study of the interplay of tissue-nonspecific alkaline phosphatase (TNAP) and NPP1 (nucleotide pyrophosphatase/phosphodiesterase-1) during catalysis of biomineralization substrates. First, we studied the incorporation of TNAP into liposomes of various lipid compositions (i.e. in pure dipalmitoyl phosphatidylcholine (DPPC), DPPC/dipalmitoyl phosphatidylserine (9:1 and 8:2), and DPPC/dioctadecyl-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
85
0
16

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(104 citation statements)
references
References 78 publications
(108 reference statements)
3
85
0
16
Order By: Relevance
“…Experiments confirmed that the interaction between detergentsolubilized TNAP, free of detergent excess, and the lipid bilayer of liposomes occurs via the GPI-anchor of the enzyme and our method of incorporation via direct insertion guarantees that the enzyme is associated with the external leaflet of the liposome membrane (Camolezi et al 2002). Enzyme incorporation is time-dependent and the incorporation yields depend of the lipid composition used to form the vesicles (Simão et al 2010a). An important point to be observed is that the enzyme bound to liposomes retains the ability to hydrolyze the different substrates, such as ATP, ADP, AMP, PP i , and p-nitrophenylphosphate (pNPP) Simão et al 2010a, b;Bolean et al 2010).…”
Section: Applications For the Study Of Lipid-protein Interactionsmentioning
confidence: 67%
See 2 more Smart Citations
“…Experiments confirmed that the interaction between detergentsolubilized TNAP, free of detergent excess, and the lipid bilayer of liposomes occurs via the GPI-anchor of the enzyme and our method of incorporation via direct insertion guarantees that the enzyme is associated with the external leaflet of the liposome membrane (Camolezi et al 2002). Enzyme incorporation is time-dependent and the incorporation yields depend of the lipid composition used to form the vesicles (Simão et al 2010a). An important point to be observed is that the enzyme bound to liposomes retains the ability to hydrolyze the different substrates, such as ATP, ADP, AMP, PP i , and p-nitrophenylphosphate (pNPP) Simão et al 2010a, b;Bolean et al 2010).…”
Section: Applications For the Study Of Lipid-protein Interactionsmentioning
confidence: 67%
“…1). By changing the type and proportion of the lipids, incubation time, method used for detergent removal, or even the velocity by which the detergent is removed, different vesicular systems can be obtained, varying in the type and quantity of proteins that can be reconstituted (Camolezi et al 2002;Ierardi et al 2002;Daghastanli et al 2004;Santos et al 2005Santos et al , 2006bRigos et al 2008Rigos et al , 2010Simão et al 2010a;Bolean et al 2010Bolean et al , 2011.…”
Section: Constructions Of Lipid Mimetic Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of relevance in the present context, APs can hydrolyze extracellular ATP via ADP and AMP to adenosine [362,363,514] (Fig. 4).…”
Section: Substrates and Catalytic Propertiesmentioning
confidence: 97%
“…Recently, it has been demonstrated that soluble heterologously expressed murine NPP1 [362,363] or NPP3 [7] hydrolyzes (at pH 7.4) PP i in addition to ATP. This result corroborates earlier observations that NPP2 cleaves PP i into P i [364].…”
Section: General Properties and Functional Rolementioning
confidence: 99%